Efficacy of continuous and intermittent phototherapy in diminution of serum total and unbound bilirubin in premature infants - Ida Bagus Mahardha Ida Bagus Mahardha (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1987)
The efficacy of continuous phototherapy (48 hours continuous light on) and intermittent Porto, S. 0., Pildes, R. S., & Goodman, H. 1969 Studies on the effect of phototherapy on neonatal hyperbilirubinemia among low birth weight infants: I. Skin colors. J. Pediat. 75:1045.9. Rubaltelli, F. F., & Carli, M. 1971 The effect of light on cutaneous bilirubin. Biol. Neonate 18:475-60. - Shirnabuku, R., & Nakamura, H. 1982 Total and unbound bilirubin determination using an automated peroxidase micromethod. Kobel. Med. Sci. 28:91-104. William, J. C., Gartner, L. M., William, O., & Stern, L. 1978 Clinical application of neonatal bilirubin binding determination: Current status./ Pediat. 93:827-32. William, J. C., & William, 0. 1982 Unbound bilirubin and kernicterus in low birth weight infants. Pediatrics 69:481-5. Zachman, R. D. 1972 Alternate phototherapy in neonatal hyperbilirubinemia. J. Pediat. 81:178-84 photo-therapy (6 hours light on, 6 hours light off 48 hours) in the diminution of serum total and unboundbilirubin levels has been studied in 26 randomized premature infants. Total-bilirubin level was determined spectrophotometrically and unbound-bilirubin level by the peroxidase oxidation method using an UB-analyzer. During phototherapy there was significant reduction of total and unbound-bilirubin levels in both groups. However, the diminution of both groups was not significantly different. After photo-therapy was completed there was significant reduction of total and unbound-bilirubin levels in both groups. The diminution of total-bilirubin level until the 4th day after treatment was not significantly different in both groups. Diminution of unbound•bilirubin of intermittent group was significantly greater than that of the continuous group in the 3rd and 4th days after treatment. In conclusion both phototherapy methods were equally effective in diminution of total and un• bound •bilirubin levels in premature infants. Key Words: phototherapy - hyperbilirubinemia - unbound-bilirubin level - premature infant - spectrophotometry